Spin-offs as Examples of Industrial and Postacademic Science Adoption - Pohulak-Żołędowska, Elżbieta (Firmy spin-off jako przykład wykorzystania nauki postakademickiej i przemysłowej, 2010)
The interaction of business sector and science institutions through the exchange of knowledge and technology has become a central concern not only for theoretical economists but also for economic policy of states in the last years. Science exerts an increasingly large influence on innovation in knowledge economy. At the same time it is worth noticing that science is also subject to transformation. From academic to post-academic or industrial science - it changes its aims and becomes more market oriented. The goal of this article is to show the importance of changes within innovation process as well as within the aims of science and its transformation. Spin-off firms are an example of post-academic science evaluation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 150-160
Keywords: innovation; university; industrial science; post-academic science